THE USE OF AIR LAYERS IN BUILDING ENVELOPES FOR ENERGY SAVING DURING AIR CONDITIONING - S. N. Osipov; S. L. Danilevskiy; A. V. Zacharenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
Since there are no large natural energy resources in Belarus, energy savings ought to be a point of the special attention. With this regard it is important to develop modern ways of savings during the process of air conditioning inside new buildings with an air layer in the enclosure, especially in translucent ones. The system of ventilation of air layers in the enclosure of a building has been introduced in which air movement is caused by the gravitational and aerodynamic forces. It makes it possible to arrange further ventilation – a natural, forced or a hybrid one. With the purpose of increasing and streamlining natural draught the partitions are used separating the different parts of air layers. For natural ventilation with the use of gravitational forces the holes in the upper and lower parts of the partitions between adjacent air layers are applied. Natural ventilation in the holes of the partitions is regulated by movable shutters, blinds or other adjusting devices. For combined or forced air exchange between adjacent zones of air layers fans are used pumping air from the air layer zones with a higher temperature to zones of air layers with lower temperature and vice versa. When air exchange is forced, in order to intensify the infiltration of air into zones of air layers jets are laid on a hard surface. In order to cool a multi-layered enclosure of a building, where the movement of air between the air layers (that have been formed by internal partitions) is being fulfilled by a natural, forced or combined mode, a part of the air or the total air processed inside the building (i.e. conditioned or non-conditioned air cooler as compared with the outside one) is being sent to these strata. Combined or forced flow of the air processed inside the building into the air layers is done through the ducts associated with the output channels of the air conditioners. The internal partitions are equipped with the air valve hole.